PENGARUH KEMUDAHAN PENGGUNAAN DAN KEANDALAN INFORMASI FITUR TEMAN BUS PADA APLIKASI MITRADARAT TERHADAP KEPUASAN PENGGUNA BCT DI KOTA BALIKPAPAN - Rafika Arina Fauziah; Riski Zulkarnain; Nasruddin Bin Idris (REKADATA, 2026)
The use of information technology in public transportation is an important strategy to improve service quality and user satisfaction. The Balikpapan City Government developed the Mitradarat application equipped with the Sahabat Bus feature as a medium for providing information on Balikpapan City Trans (BCT) services. However, the level of user satisfaction is greatly influenced by the ease of use of the application and the reliability of the information presented. This study aims to analyze the effect of ease of use and information reliability on BCT user satisfaction in Balikpapan City. The study used a quantitative approach with a survey method of BCT users who had used the Sahabat Bus feature. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that ease of use and information reliability had a positive and significant effect, both partially and simultaneously, on user satisfaction. These findings emphasize the importance of developing public transportation applications that are easy to use and provide accurate and timely information to increase satisfaction and sustainability of service use.